Persepsi Guru tentang Kurangnya Penggunaan Media Pembelajaran dalam Proses Pembelajaran di SD Negeri Sungayang - Lestari Lestari; Nur Asiah; Safrizal Safrizal (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
The urgency of this research stems from the knowledge gap regarding contextual factors contributing to the underuse of learning media in rural elementary schools, which has not been adequately addressed in previous research, which has tended to focus on urban contexts. This study aims to examine teachers' perceptions at Sugayang Public Elementary School regarding the underuse of learning media in the learning process, as well as the factors that contribute to it. The method used was a descriptive qualitative method, utilizing in-depth interviews as a data collection technique. The data were then analyzed using data reduction, data display, and conclusion drawing techniques according to Miles and Huberman. The results showed that teachers experienced difficulties in using technology, difficulties in creating learning media, and the perception that using media was time-consuming. This reveals an important pattern that the underuse of learning media is a systematic problem rooted in the TPACK gap that is not supported by practical time management solutions. These findings imply that changes in learning practices will not occur simply through the provision of generic technology tools or training; rather, bottom-up and contextual solutions are needed. The novelty of this research lies in the in-depth qualitative approach applied to the under-researched context of rural elementary schools, which has not been studied before. This research contributes through recommendations for the implementation of a peer-mentoring program and the development of a ready-to-use digital learning media bank, thus offering valuable insights for future research with relevant stakeholders.